Pattern of medical care for diarrheal patients in Dacca urban area - Khan, Moslemuddin, 1930- (Scientific report (Cholera Research Laboratory) ;, 1977)
Report of a 1974-1976 survey conducted among 1645 patients admitted in the Cholera Research Laboratory, Dacca.